Kerjasama Pemerintah Kabupaten Purworejo dan Masyarakat dalam Pengembangan Desa Wisata Kaligono Kecamatan Kaligesing Kabupaten Purworejo - Nida - Ulfa; Muhammad - Adnan; Ahmad - Taufiq (Journal of Politic and Government Studies, 2018)
ABSTRACT The success of the development of the national tourism sector is strongly supported by the role of regional tourism development potential. Since the policy on tourism, tourism village development in Indonesia began to emerge one of them is Kaligono Tourism Village. The development of a tourist village demands coordination and cooperation and a balanced role between the government, the private sector and the community. This study aims to describe the cooperation implemented by the Government of Purworejo Regency and the community in the development of Kaligono Tourism Village. This research is a descriptive research with qualitative approach. Sources / subjects of this research include Head of Promotion and Cooperation of Tourism and Culture Office of Purworejo Regency, Kaligono Village Government, Pokdarwis Dewi Kano manager, Pokdarwis Nuansa Alam, Pokdarwis Joko Kendhil , visitors and community. The data were collected using observation, interview, and documentation study.The results showed that the cooperation between the community and the Department of Tourism and Culture is not optimal due to the absence of MoU agreed by both parties. The reality of cooperation between the people of Kaligono Tourism Village and the Regional Government of Purworejo Regency is manifested in the form of training and coaching. Cooperation does not affect the improvement of tourism facilities. The facility is actually built by the community and PNPM Tourism aid for three consecutive years. In addition, based on the findings of researchers positive impact of the existence of tourist villages such as improving the economy of the community, the creation of jobs and environmental sustainability is the result of high awareness and community participation, not the result of cooperation between the community and the Department of Tourism and Culture. Keywords: Cooperation, Village Tourism Development, The Role of Government, The Role of Society